Implementasi Kebijakan Trans Metro Bandung (TMB) Dalam Upaya Meningkatkan Pelayanan Transportasi Publik Di Kota Bandung - Kartika; Taryono, Ono; Marganda Aritonang, Dinoroy; Anggun Artisa, Rike (Jurnal Administrasi Publik dan Pemerintahan, 2024)
Traffic congestion is one of the critical problems faced by Bandung City as the center of socio-economic activities in West Java. To address this issue, the Bandung City Government has implemented the Trans Metro Bandung (TMB) policy as a mass public transportation mode based on bus rapid transit (BRT). However, the effectiveness of this policy is still in question considering the low level of public transportation usage and the suboptimal services provided. This study aims to analyze the implementation of the Trans Metro Bandung policy based on George C. Edwards III's implementation model, which includes four main variables: communication, resources, implementers’ disposition, and bureaucratic structure. The approach used is descriptive qualitative with data collection techniques through interviews, observations, and document studies. The results show that policy communication to the public has not been effective, resources such as fleets and bus stop infrastructure are still limited, implementers have a positive disposition but lack continuous training support, and the bureaucratic structure is fragmented without strong cross-sectoral coordination. These four factors are interrelated and serve as the main obstacles to the success of TMB implementation. This study contributes theoretically to strengthening public policy implementation based on Edwards III's model and recommends improvements in public communication, resource enhancement, and bureaucratic governance reform in Bandung City's transportation sector.